Estudio de la Inﬂuencia de la Geometría del Difusor de Entrada en la Operación de un Motor Ramjet por Medio de Software de Dinámica de Fluidos Computacional - Cerpa, Rafael; Ortiz, Niyiret; Portillo, Alejandra (TECCIENCIA, 2020)
This investigation delivers the results of the study in two dimensions of the inﬂu- ence of the geometry at the entrance of the diﬀuser of a ramjet engine using the ANSYS-Fluent software. Initially, the isentropic, thermal and gas dynamics ﬂow calculations were performed in order to obtain the ramjet operational parameters; from these results, diﬀerent geometries at the entrance of the diﬀuser were pro- posed, which in this particular case has a central core, whose main function is the generation of oblique shock waves in order to make the diﬀusion process gradually without generating great amount of losses. The proposed geometries were simu- lated through the ANSYS -Fluent software in order to know their inﬂuence on the isentropic ﬂow behavior. Finally, it was possible to verify that the variation of the wedge angle is given between 7º-14º without aﬀecting the behavior of the ramjet diﬀuser.